Rare microbial taxa as the major drivers of ecosystem multifunctionality in long-term fertilized soils - Chen, Qing-Lin; Ding, Jing; Zhu, Dong; Hu, Hang-Wei; Delgado-Baquerizo, Manuel; Ma, Yi-Bing; He, Ji-Zheng; Zhu, Yong-Guan (Soil biology & biochemistry, 2020)
Soil microbial communities play an essential role in driving multiple functions (i.e., multifunctionality) that are central to the global biogeochemical cycles. Long-term fertilization has been reported to reduce the soil microbial diversity, however, the impact of fertilization on multifunctionality and its relationship with soil microbial diversity remains poorly understood. We used amplicon sequencing and high-throughput quantitative-PCR array to characterize the microbial community compositions and 70 functional genes in a long-term experimental field station with multiple inorganic and organic fertilization treatments. Compared with inorganic fertilization, the application of organic fertilizer improved the soil multifunctionality, which positively correlated with the both bacterial and fungal diversity. Random Forest regression analysis indicated that rare microbial taxa (e.g. Cyanobacteria and Glomeromycota) rather than the dominant taxa (e.g. Proteobacteria and Ascomycota) were the major drivers of multifunctionality, suggesting that rare taxa had an over-proportional role in biological processes. Therefore, preserving the diversity of soil microbial communities especially the rare microbial taxa could be crucial to the sustainable provision of ecosystem functions in the future. [Display omitted] •Inorganic fertilization decreased soil multifunctionality.•Organic fertilization increased microbial diversity and multifunctionality.•Rare microbial taxa had an over-proportional role in multifunctionality.